Comparative proteomic analysis of mitochondrial proteins from maize CMS‐C sterile, maintainer and restorer anthers. Issue 2 (22nd May 2020) - Zhang, Huaisheng; Wang, Bin; Li, Bing; Lin, Yanan; Yang, Huili; Ding, Dong; Xue, Yadong; Tang, Jihua
Abstract: The maize C system of cytoplasmic male sterility (CMS) and its fertility restoration gene Rf4 have been widely used for maize hybrid production; however, the underlying mechanism is still uncertain. The sterility factor functions in mitochondria, where it interacts directly or indirectly with the restorer. Mitoproteomics can capture all participants involved in CMS and restoration at the organelle level. In the present study, we identified and quantified anther mitochondrial proteins from CMS, maintainer and restorer lines. We obtained 14, 528 unique peptides belonging to 3, 369 proteins. Comparative analysis of 1840 high‐confidence proteins revealed 68 were differentially accumulated proteins likely involved in CMS or its restoration within mitochondria. These proteins were mainly associated with fatty acid metabolism, amino acid metabolism and protein‐processing pathways. These results suggest that an energy deficiency caused by the sterility factor hinders other proteins or protein complexes required for pollen development through nuclear‐mitochondrial interaction. The restorer factor may boost the energy generation by activating alternative metabolic pathways and by improving the post‐translation processing efficiency of proteins in energy‐producing complexes to restore pollen fertility. Our findings may aid detailed molecular analysis and contribute to a better understanding of maize CMS‐C restoration and sterility.